2018
DOI: 10.1152/ajplung.00379.2017
|View full text |Cite
|
Sign up to set email alerts
|

Human lung branching morphogenesis is orchestrated by the spatiotemporal distribution of ACTA2, SOX2, and SOX9

Abstract: Lung morphogenesis relies on a number of important processes, including proximal-distal patterning, cell proliferation, migration and differentiation, as well as epithelial-mesenchymal interactions. In mouse lung development, SOX2 cells are localized in the proximal epithelium, whereas SOX9 cells are present in the distal epithelium. We show that, in human lung, expression of these transcription factors differs, in that during the pseudoglandular stage distal epithelial progenitors at the tips coexpress SOX2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 18 publications
10
127
0
Order By: Relevance
“…We, and others, have recently shown that distal tip buds in the early human lung coexpress SOX2 and SOX9 as opposed to only SOX9 in mice . Moreover, we showed that the maintenance of this double‐positive population is required for branching morphogenesis . Here, our results demonstrated that FGF10 impaired the balance and colocalization of SOX2/SOX9 and impaired branching in the early (10–12 weeks) human lung.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We, and others, have recently shown that distal tip buds in the early human lung coexpress SOX2 and SOX9 as opposed to only SOX9 in mice . Moreover, we showed that the maintenance of this double‐positive population is required for branching morphogenesis . Here, our results demonstrated that FGF10 impaired the balance and colocalization of SOX2/SOX9 and impaired branching in the early (10–12 weeks) human lung.…”
Section: Discussionsupporting
confidence: 73%
“…HTII280 did not always colocalize with pro-SFTPC, supporting previous reports that HTII-280 may also be expressed in undifferentiated epithelium [29]. Furthermore, we had previously established that smooth muscle cells (SMCs) appear to promote SOX2+ cells and suppress the SOX9+ population [16]. Given the expansion of SOX9+ cells in the FGF-treated explants, we assessed the expression of SMCs using immunostaining for ACTA2.…”
Section: Fgf Treatments Altered the Coexpression Of Sox2/sox9 Double-supporting
confidence: 70%
See 1 more Smart Citation
“…3B). By contrast, in human lungs SOX2 is consistently co-expressed with SOX9 in tip cells throughout the pseudoglandular stage (Danopoulos et al, 2018; Miller et al, 2017; Nikolić et al, 2017). As human cells exit the tip progenitor domain and start to differentiate along airway lineages, they turn off SOX9, but retain SOX2 (Fig.…”
Section: Studies Of Human Lung Development Using Human Lung Tissuementioning
confidence: 86%
“…Recently, a large study that examined lung structure in >3000 individuals reported that developmental variation in human lung branching, specifically a central airway branch variation, is associated with chronic obstructive pulmonary disease (COPD) (Smith et al, 2018). Moreover, one of these airway branch variations is associated with genetic polymorphisms within the FGF10 gene, which is known to be crucial for branching morphogenesis in the developing lung (Bellusci et al, 1997; Danopoulos et al, 2018; Park et al, 1998; Peters et al, 1994). …”
Section: Introductionmentioning
confidence: 99%